Radical Duality Ⅳ (2023)
"Radical Duality" is a practical approach based on my own ontology beyond arguments of “eternal return” (Deleuze) and speculative realism. In this ontology, I find the philosophical idea of “the Time after that” an extremely creative concept of time, a concept that is emblematic of capitalism’s dynamism. Within this artistic practice, then, three elements, “Media,” “Theme,” and “Method” define creative acts, thus correlating to each other. Any medium used for creative activities is a variable (in this piece, just sound). “Method” is a factor which strongly describes the characteristics of a creator. This, in turn, poses questions about relations. “Method” determines the relations between media, and “Media” change themselves according to “how these media relate to each other,” so every artist should think about “what the meaning of the relating is.” For myself, the relation is “a multiplicity of radical duality which consists of the discrete and the continuous.” For this piece, I first made a patch with MAX/MSP. In this patch, then, I created two primitive faders ― “the discrete” and “the continuous” ―, whose values affect the whole sound. Additionally, I made four more faders ― “continuation of discreteness”, “discreteness of continuation”, “continuation of continuation”, and “discreteness of discreteness” ― whose values change various parameters of this complex patch. Also, I quoted Franz Schubert’s 7th symphony and JS Bach's “Dona nobis pacem” for expressing a “bottomless void” as "Theme", where the story progresses from hardship to relief. Since “Radical Duality” treats media as variables, those variables do not have to be limited to music. We can treat visuals, concepts, digital content, bodies, photos and so on as media, then change these forms completely, defining new relations each time.